Polymorphism of intron‐1 in the voltage‐gated sodium channel gene of Anopheles gambiae s.s. populations from Cameroon with emphasis on insecticide knockdown resistance mutations - JOSIANE ETANG; JOSE L. VICENTE; PHILIPPE NWANE; MOUHAMADOU CHOUAIBOU; ISABELLE MORLAIS; VIRGILIO E. DO ROSARIO; FREDERIC SIMARD; PARFAIT AWONO‐AMBENE; JEAN CLAUDE TOTO; JOAO PINTO (Molecular Ecology, 2009)
Sequence variation at the intron‐1 of the voltage‐gated sodium channel gene in Anopheles gambiae M‐ and S‐forms from Cameroon was assessed to explore the number of mutational events originating knockdown resistance ( kdr ) alleles. Mosquitoes were sampled between December 2005 and June 2006 from three geographical areas: (i) Magba in the western region; (ii) Loum, Tiko, Douala, Kribi, and Campo along the Atlantic coast; and (iii) Bertoua, in the eastern continental plateau. Both 1014S and 1014F kdr alleles were found in the S‐form with overall frequencies of 14% and 42% respectively. Only the 1014F allele was found in the M‐form at lower frequency (11%). Analysis of a 455 bp region of intron‐1 upstream the kdr locus revealed four independent mutation events originating kdr alleles, here named MS1 ‐1014F, S1‐1014S and S2‐1014S kdr‐ intron‐1 haplotypes in S‐form and MS3‐1014F kdr‐ intron‐1 haplotype in the M‐form. Furthermore, there was evidence for mutual introgression of kdr 1014F allele between the two molecular forms, MS1 and MS3 being widely shared by them. Although no M/S hybrid was observed in analysed samples, this wide distribution of haplotypes MS1 and MS3 suggests inter‐form hybridizing at significant level and emphasizes the rapid diffusion of the kdr alleles in Africa. The mosaic of genetic events found in Cameroon is representative of the situation in the West–Central African region and highlights the importance of evaluating the spatial and temporal evolution of kdr alleles for a better management of insecticide resistance.